NURSES’ ROLES IN HEALTH PROMOTION PRACTICE: A SYSTEMATIC REVIEW - Budi Widiyanto (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Promoting public health is applied by health care professionals including nurses. The focus of health promotion by nurses traditionally has been on disease prevention and changing the client behavior with respect to their health. In fact, the role as promoters of heath by nurses is not as simple as we perceive. It is because they have experience and multi-disciplinaryknowledge of health promotion in their nursing practice. Aims: This study presents a systematic review aimed at examining the findings of existing research studies (2001-2016) of health promotion roles by nurses. Methods: A systematic search of databases using EBSCOhost, ProQuest, and Science Direct were conducted. The 353 articles included were extracted and verified and a new interpretation of the concepts extracted was generated. Results: 12 research articles met the inclusion criteria and included in this review. Nurses play an important role in relation to health promotion in any setting like hospital, community, primary care and home care. Conclusion: This review need to be confirmed by well-designed large studies which engage validated procedures of nurses’ role in health promotion practice and involve multivariate analyses to make sure the real role of nurses regarding health promotion practice.